ANALYSIS OF THE DEVELOPMENT OF FUTURE PHYSICAL EDUCATION TEACHERS' KNOWLEDGE OF SPORTS TOURISM IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical and methodological foundations of the development of the knowledge of the future physical education teachers about tourism are studied. Also, the development of future physical education teachers' knowledge of sports tourism in New Uzbekistan was analyzed.